Heterozygous SOD1 deficiency in mice with an NZW background causes male infertility and an aberrant immune phenotype. (2nd December 2019) - Homma, Takujiro; Takeda, Yuji; Sakahara, Satoshi; Ishii, Naoki; Kobayashi, Sho; Abe, Hiroyuki; Asao, Hironobu; Fujii, Junichi
Abstract: New Zealand white (NZW) mouse is a mutant strain that has a larval defect in the immune system, and a F1 hybrid between NZW and New Zealand Black mouse spontaneously develops systemic lupus erythematosus (SLE). In meantime, the ablation of superoxide dismutase 1 (Sod1) causes autoimmune haemolytic anaemia, a clinical condition of SLE, in mice with a C57BL/6 background. On the basis of our previous studies, we hypothesised that oxidative stress may trigger this aberrant autoimmunity in NZW mice without crossing with another strain. To validate this, we attempted to establish Sod1 −/− /NZW mice but this attempt failed to obtain any objective mouse. The congenic Sod1 +/− /NZW male mice were completely infertile because of severe oligozoospermia attributed to a defect in spermatogenesis. The levels of the SOD1 protein were about a half in the testes of the Sod1 +/− /NZW mice. Sperm from the Sod1 +/− /NZW mice were largely defective and showed quite low fertilising ability in in vitro fertilisation assays. Concomitant with an increase in the oxidatively modified proteins, spermatogenic cells underwent more cell death in the testes of the Sod1 +/− /NZW mice compared to those of WT/NZW mice. An examination of immunocompetent cells from Sod1 +/− /NZW mice indicated an abnormality in T-cell responses. These collective results suggest that the oxidative stress caused by an SOD1 haploinsufficiency exerts deleterious effects on the testis, either directly on spermatogenic cells or via the destabilisation of the autoimmune response in Sod1 +/− /NZW mice.